Makna dalam Lirik Lagu ‘Halu’ Karya Feby Putri: Analisis Semiotika Ferdinand de Saussure - Ulfah Ulfah; Dwi Wahyu Chandra Dewi (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study analyzes the symbolic meaning in the lyrics of the song "Halu" by Feby Putri using Ferdinand de Saussure's semiotic approach. The purpose of the study is to reveal the relationship between the signifier and the signified in the song lyrics to understand the emotional and cultural messages contained therein. The method used is descriptive qualitative analysis with a focus on linguistic signs in the lyric text. The results of the study show that the song "Halu" utilizes metaphors (such as "candu" and "bayang-bayang") to represent one-sided love, illusion, and emotional alienation. The lyrics of the song are not only a personal expression of the creator, but also reflect the collective experience of the younger generation in interpreting unrealized relationships. This study concludes that popular music, through its semiotic structure, functions as a complex medium of cultural communication. Suggestions for further research include exploring the interaction of musical elements with lyrics and the application of other semiotic theories to enrich the analysis. These findings also emphasize the importance of media literacy in understanding music not only as entertainment, but also as a cultural product that is full of meaning.